Studying faculty members’ readiness to use Shaqra University e-learning platform - Raed Alotaibi; Abdulrahman Alghamdi (Institute of Advanced Engineering and Science, 2021)
In Saudi Arabia, most universities are seeking to implement e-learning to improve education access and processes. Although some universities have already implemented e-learning, most have not. Shaqra University is aiming to implement an e-learning system. Therefore, through the use of a questionnaire, this study examines faculty members’ readiness to use the e-learning platform and assesses their readiness based on gender differences and user experience. Factors considered were usage self-efficacy, self-confidence in dealing with e-learning, Attitude towards e-learning and educational needs towards e-learning. The results revealed that, based on all these factors, faculty members were ready to use the platform of e-learning. There were no differences between male and female participants in self-efficacy in using information and communications technology, self-confidence in e-learning and educational needs towards e-learning. The females’ mean score was significantly higher than the males’ mean score. Between faculty members with no experience and faculty members’ who were experienced in e-learning, user experience was significantly different for self-efficacy of using information and communications technology, self-confidence in e-learning and attitude towards e-learning. These results revealed that faculty members are ready to use a platform of e-learning and these results may help decision makers in Shaqra University to successfuly adopt an e-learning platform.